PENINGKATAN KUALITAS PELAYANAN MELALUI INOVASI PELAYANAN PUBLIK BIDANG ADMINISTRASI: (Studi pada Aplikasi Poedak Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gresik) - Marwiyah, Siti; Rahmadi, Andhi Nur; Ansori, Faisal (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
The development of information technology and the demands of the majority of society for services have encouraged the government to carry out digital transformation by creating innovation and improvements in public services to improve the quality of the services themselves. The Gresik Regency Population and Civil Registration Department is currently developing services through the poedak website which is used in managing population administration documents. This research is a qualitative descriptive method that describes the implementation of Poedak innovation and analysis of the quality of administrative services through the Poedak website which is based on the service quality theory according to Tcipto. The results of this research show that the implementation of the Poedak website is a form of the Gresik Regency Dispendukcapil office in encouraging e-Government in services. With this Poedak website, it is hoped that the public will be able to submit documents online without having to come to the Dispendukcapil office directly so that it is time and cost effective. If it is based on service quality with theoretical indicators of responsiveness, assurance, empathy, it has worked well and in accordance with service criteria. However, in terms of reliability indicators in the service process, it was found that employees still tend to rush in explaining services, so this is what causes input errors because people still don't fully understand what is meant. In terms of Tangibles indicators, waiting room facilities are still considered to be poor because they do not prioritize the comfort of the community as service recipients. Keywords: Service Quality, Public Service, Poedak.